Implementation of the Constitutional-Legal Task to Ensure Uniform Application of Legal Norms by the Court of Cassation in the Civil Procedure - Hovhannisyan , V. (Bulletin of Yerevan University C: Jurisprudence, 2016)
The peculiarities of the constitutional-legal task to ensure uniform application of legal norms by the court of Cassation in the civil procedure have been thoroughly analyzed in the article presented. As a result of comprehensive research of constitutional-legal status of the court of Cassation the author has hereby found that conditions and reasonable limitations of access to the court of Cassationt are primarily conditioned by the necessity of realization of constitutional tasks of the latter and directly reflect their individual practices. It has been underlined that the function of the court of Cassation on promotion of the law development has a formal nature, as this court instance does not establish new rules of conduct and there are no clear legal mechanisms provided in RA legislation for making interpretations of legal norms by competent law-making bodies binding. The author has concluded that it would be better to refer primarily to the fulfilment of constitutional task regarding insuring by the court of Cassation of the uniform application of law, as trade usages also establish rules of conduct. Facilitation of development of law in civil procedure shall be examined beyond the scope of constitutional-legal objective of the court of Cassation, as in this case uniform application of law is of paramount importance. Precise legal guarantees shall be established by RA legislation and the court of Cassation shall be granted with sufficient legal tools for full-fledged implementation of its tasks and main functions.
Keywords: court of Cassation, uniform application of legal norms, law development, constitutional-legal task, cassation proceedings, supervisory proceedings, condition of appeal